2019
DOI: 10.3390/ijms20153681
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p53 Family Structure and Function in Non-Canonical Response Element Binding and Activation

Abstract: The p53 canonical consensus sequence is a 10-bp repeat of PuPuPuC(A/T)(A/T)GPyPyPy, separated by a spacer with up to 13 bases. C(A/T)(A/T)G is the core sequence and purine (Pu) and pyrimidine (Py) bases comprise the flanking sequence. However, in the p53 noncanonical sequences, there are many variations, such as length of consensus sequence, variance of core sequence or flanking sequence, and variance in number of bases making up the spacer or AT gap composition. In comparison to p53, the p53 family members p6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 130 publications
(150 reference statements)
3
21
0
Order By: Relevance
“…However, our study indicated that p53 may affect the reporter activity of the reporter vector containing the DNA fragment (−567 to −363), which does not have a putative p53 binding site. The majority of gene expressions modulated by p53 generally occurred through consensus sequences other than that of the p53 DNA-binding site [42,43]. Our results confirmed that maspin is a target gene of PTEN and p53, and should be referred to as an anti-tumor gene in bladder carcinoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…However, our study indicated that p53 may affect the reporter activity of the reporter vector containing the DNA fragment (−567 to −363), which does not have a putative p53 binding site. The majority of gene expressions modulated by p53 generally occurred through consensus sequences other than that of the p53 DNA-binding site [42,43]. Our results confirmed that maspin is a target gene of PTEN and p53, and should be referred to as an anti-tumor gene in bladder carcinoma cells.…”
Section: Discussionsupporting
confidence: 77%
“…ing between the two half-sites, ranging from 0-13 bp 8,9 . Hence the helical phasing between the two half sites could differ, which has the potential to impact the binding of p53 to DNA or the kinetic stability of complexes.…”
Section: Increasing the Spacing Between Half Sites Impacts The Populamentioning
confidence: 99%
“…Disrupting the helical phasing between half sites destabilizes tetrameric p53/DNA complexes p53 REs can have variable spacing between the two half-sites, ranging from 0-13 bp (8,9). Hence, the helical phasing between the two half sites can differ, potentially impacting the binding of p53 to DNA or the kinetic stability of complexes.…”
Section: P53 Tetramers Bind To Dnas Containing Either One or Two Halfmentioning
confidence: 99%
“…To activate transcription, p53 must recognize and bind to p53 REs in DNA. The p53 RE is composed of two 10 bp half site sequences with 0 to 13 base pairs of spacing in between (8,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation